Intervertebral Lumbar Spine Kinematics in Chronic Low Back Pain Patients Measured Using Biplane Radiography - William Anderst; C. James Kim; Kevin M. Bell; Tom Gale; Cate Gray; Carol M. Greco; Clarissa LeVasseur; Gina McKernan; Sabreen Megherhi; Charity G. Patterson; Sara R. Piva; Caroline Pellegrini; et al. (JOR Spine, 2025)
ABSTRACT Background Chronic low back pain (cLBP) presents as a heterogeneous condition, making diagnosis and treatment challenging. Lumbar spine intervertebral kinematics may provide an objective assessment of patients with cLBP that may be used to inform treatment decisions and evaluate the efficacy of interventions. The purpose of this study was to provide a quantitative description of intervertebral motion in the lumbar spine during flexion/extension (F/E) and lateral bending (LB) in individuals with cLBP. Methods Data from 125 individuals is included in this analysis (M: 53; F: 72; n = 66 < 60 years of age; average BMI: 25.7 ± 3.6 kg/m2). Dynamic biplane radiography (DBR) and a validated volumetric model‐based tracking system were used to assess intervertebral motion at every lumbar level (L1‐L2 through L5‐S1) during active F/E and LB movements in individuals with cLBP. The outcome measures were the intervertebral translation and rotation range of motion (ROM), the contribution of each motion segment to lumbar motion, the anterior–posterior slip per degree of flexion (SPDF), and trial‐to‐trial repeatability as assessed by the standard deviation in continuous kinematics waveforms over 3 trials of each movement. Outcomes were calculated for the entire group as well as for the subgroups of men, women, individuals less than 60 years of age, and individuals 60 or more years of age. Results The mean intervertebral F/E ROM progressively increased from 6.8° ± 3.1° at the L1‐L2 through the L4‐L5 motion segments, then decreased from 9.7° ± 5.2° at L4‐L5 to 8.4° ± 4.9° at L5‐S1. However, substantial variability among individuals was observed, and only 7 participants (5.6%) followed this ROM pattern. The mean intervertebral LB ROM increased from 8.8° ± 3.2° at L1‐L2 to 9.1° ± 4.2° at L2‐L3 and then progressively decreased from the L2‐L3 through the L5‐S1 motion segments to 2.7° ± 1.8°. However, only 13 participants (10.4%) followed this ROM pattern. On average, the L1‐L2, L2‐L3, and L5‐S1 motion segments were the main contributors to F/E when the torso was near the upright neutral position. L2‐L3, L3‐L4, and L4‐L5 were the main contributors to midrange flexion and extension, and L3‐L4, L4‐L5, and L5‐S1 were the main contributors to lumbar motion when the trunk was near full flexion. L1‐L2 and L2‐L3 were the main contributors to lumbar LB near the neutral position and through the midrange. The contributions from L4‐L5 and L5‐S1 peaked at the neutral position and at maximum bending. SPDF was similar in the L1‐L2, L2‐L3, and L3‐L4 motion segments, but less in the L4‐L5 motion segment. L5‐S1 SPDF was characterized by high variability among individuals as compared to other motion segments. The average trial‐to‐trial repeatability in intervertebral rotation in the primary plane of motion over all points on the kinematics waveform ranged from 0.3° to 0.7° across all motion segments during F/E and LB. Conclusion This study demonstrates the heterogeneity in lumbar spine intervertebral kinematics in individuals with cLBP. Further research is needed to identify mechanistic links between kinematics and other biological, behavioral, and clinical features in individuals with cLBP and to identify which kinematic characteristics are useful metrics for informing treatment approaches for patients with cLBP.